FOREIGN POLICY CIRCUMSTANCES OF THE THIRD REICH EMERGENCE IN 1930s - Aleksej Anikeev (Гуманитарные и юридические исследования)
One of the most important problems of modern international historiography of Nazi Germany is the identification of the ideological, economic and military-political foundations for the emergence of the Third Reich. The article examines ideological and political doctrines, the principles of domestic and foreign policy, economics and military organization, which served the basis for the state structure of National Socialist Germany. The author analyzes the ideological concepts of the Third Reich ideologists (A. Rosenberg, A. Hitler, J. Goebbels), the main principles of the foreign policy doctrine of the Nazis. Based on sources, the main stages of Nazi foreign policy activity are considered prior to the outbreak of World War II. The main directions of the Third Reich foreign policy in 1933-1935 and in 1936-1939 are studied. The diplomatic, military-political and economic measures aimed at canceling the terms of the Treaty of Versailles in 1919 are analyzed, and the reaction of the representatives of European states to the unilateral withdrawal of Germany from the Versailles agreements is shown. The main directions of the foreign policy of Nazi Germany after the collapse of the Versailles system are considered: the problem of armament of the German army, Germany's refusal to comply with the terms of the 1921 Rhine Warranty Pact (the introduction of troops into the demilitarized Rhineland), the attempt and implementation of the Anschluss of Austria in 1934 and in 1938, support for the Franco in the civil war in Spain, the emergence of military-political alliance of Nazi Germany with fascist Italy and Japan, which led to the formation of axos powers (the "axis" country, the "Rome-Berlin-Tokyo axis") and the beginning of World War II.